60-th anniversary of Vitaliy Yuriyovych Denysov - Institute for Nuclear Research (Âderna Fìzika ta Energetika, 2019)
Brief biography and scientific achievements of Vitaliy Yuriyovych Denysov in relation with his 60-th anniversary.